2005
DOI: 10.1159/000085854
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Patients with Antineutrophil Cytoplasmic Autoantibody-Associated Vasculitis with Renal Involvement

Abstract: Background: Despite treatment, renal involvement in antineutrophil cytoplasmic autoantibody (ANCA)-positive vasculitis is still associated with significant long-term mortality and remains an important cause of end-stage renal failure. Methods: We retrospectively analyzed a series of 61 consecutive patients with newly diagnosed ANCA-associated renal vasculitis (54.1% Wegener’s granulomatosis, 23% renal-limited vasculitis, 16.4% microscopic polyangiitis, 4.9% Churg-Strauss syndrome) diagnosed between 1986 and 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
4
19
1
1
Order By: Relevance
“…[16] In patients with AAV, renal insufficiency is also connected with poor prognosis. [17,18] Because our ICU forms an integral part of a nephrology unit, where most of our patients were recruited from, renal insufficiency was present in all our patients, without exception. Acute renal failure or insufficiency was registered in 13 patients, 11 of whom required renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[16] In patients with AAV, renal insufficiency is also connected with poor prognosis. [17,18] Because our ICU forms an integral part of a nephrology unit, where most of our patients were recruited from, renal insufficiency was present in all our patients, without exception. Acute renal failure or insufficiency was registered in 13 patients, 11 of whom required renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Data on this matter remain, however, inconclusive. 92,[96][97][98] In addition to renal fibrosis, an association between lung fibrosis and MPO-ANCA has been observed. [99][100][101] Pulmonary fibrosis in PR3-AAV seems to occur less often.…”
Section: Histopathologic Featuresmentioning
confidence: 99%
“…96,[132][133][134][135] A systematic review demonstrated worse patient survival in patients with MPA compared with patients with GPA. 136 In our patients with AAV who had renal involvement, patient survival was worse in patients with MPO-AAV (n=92) compared with patients with PR3-AAV (n=89), whereas renal survival was similar (P50.28).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized that there are meaningful clinical differences between patients with PR3-AAV and MPO-AAV and it has been suggested that PR3-AAV and MPO-AAV are distinct diseases because PR3-ANCA-positive and MPO-ANCA-positive patients demonstrate a different disease spectrum (2,6,7). In general, patients with PR3-ANCA have more widespread extrarenal organ involvement and more active renal lesions at the time of diagnosis compared with MPO-ANCA-positive patients who have more chronic lesions (2,8,9). Another important difference is the higher relapse rate found in PR3-ANCA-positive AAV patients, which may be a major prognostic factor for renal survival during long-term follow-up (3).…”
Section: Introductionmentioning
confidence: 99%